2009
DOI: 10.1097/mcd.0b013e3283186907
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death in spondylo-meta-epiphyseal dysplasia, short limb-abnormal calcification type

Abstract: The spondylo-meta-epiphyseal dysplasias are an expanding group of skeletal dysplasias with specific features differentiating each subtype. We review the precocious carpal mineralization, unique metacarpal shape, triangular distal phalanges and mushroom cloud-shaped proximal phalanges present at an early age in spondylo-meta-epiphyseal dysplasia, short limb-abnormal calcification type (SMED SL-AC) and report two patients with clinical and radiographic features consistent with SMED SL-AC, who died suddenly becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…CNS: Compression of the cervical spinal cord due to foramen magnum stenosis in about 50% of the patients. 117 Additionally, hypomyelination in 1 patient. 118 Osteodysplasty Melnick-Needles (OMIM: 309350) General information: Less than 70 patients reported.…”
Section: Spondylo-epi-metaphyseal Dysplasia Short Limb-abnormal Calcmentioning
confidence: 97%
See 1 more Smart Citation
“…CNS: Compression of the cervical spinal cord due to foramen magnum stenosis in about 50% of the patients. 117 Additionally, hypomyelination in 1 patient. 118 Osteodysplasty Melnick-Needles (OMIM: 309350) General information: Less than 70 patients reported.…”
Section: Spondylo-epi-metaphyseal Dysplasia Short Limb-abnormal Calcmentioning
confidence: 97%
“…CNS: Compression of the cervical spinal cord due to foramen magnum stenosis in about 50% of the patients . Additionally, hypomyelination in 1 patient …”
Section: Glossarymentioning
confidence: 99%
“…A previous study [5] suggested that SMED-SL should be included in the list of genetic disorders causing death. In genetic diseases caused by the impaired function of a single gene, various interconnected pathways are affected, making the identification of relevant pharmaceutical targets difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This bone dysplasia is progressive, with serious complications leading to death in some cases. Atlantoaxial instability resulting in cord damage has been the most reported cause of death [2,5]. Homozygous mutations occurring in the Discoidin domain receptor 2 gene ( DDR2 , MIM 191311) have been identified as the cause for this severely dwarfing condition [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of chondral calcification was emphasized by Langer et al [] who proposed the name SMED, SL‐AC. The lack of soft tissue and chondral calcification on first examination cannot exclude the diagnosis of SMED, SL‐AC since these findings may appear later in life [Al‐Gazali et al, ; Dias et al, ]. The loss of function of DDR2 (Discoidin domain receptors 2) is responsible of this disease [Bargal et al, ].…”
Section: Introductionmentioning
confidence: 99%